2018
DOI: 10.1039/c8nr03394c
|View full text |Cite
|
Sign up to set email alerts
|

Cu dimer anchored on C2N monolayer: low-cost and efficient Bi-atom catalyst for CO oxidation

Abstract: By means of density functional theory (DFT) computations, we systemically investigated CO/O2 adsorption and CO oxidation pathways on a bi-atom catalyst, namely, a copper dimer anchored on a C2N monolayer (Cu2@C2N), and we compared it with its monometallic counterpart Cu1@C2N. The Cu dimer could be stably embedded into the porous C2N monolayer. The reactions between the adsorbed O2 and CO via both bi-molecular and tri-molecular Langmuir-Hinshelwood (L-H) and Eley-Rideal (E-R) mechanisms were comparably studied,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 82 publications
2
43
0
Order By: Relevance
“…Previous theoretical studies showed that the single-atom catalyst Fe 1 @C 2 N [54] and biatom catalyst Cu 2 @C 2 N possess good performance for CO oxidation. [48] Thus, we constructed the homonuclear biatom species Fe 2 @C 2 N and the heteronuclear analogue Fe 1 Cu 1 @C 2 N in this study.…”
Section: Geometries and Thermodynamic Stabilities Of The M 1 M 2 @C 2mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous theoretical studies showed that the single-atom catalyst Fe 1 @C 2 N [54] and biatom catalyst Cu 2 @C 2 N possess good performance for CO oxidation. [48] Thus, we constructed the homonuclear biatom species Fe 2 @C 2 N and the heteronuclear analogue Fe 1 Cu 1 @C 2 N in this study.…”
Section: Geometries and Thermodynamic Stabilities Of The M 1 M 2 @C 2mentioning
confidence: 99%
“…We first examined the energetically most favorable anchoring site of Fe on the C 2 N monolayer, for which three possible anchoring sites [48] were considered. In the lowest energy configuration of Fe 1 @C 2 N, the Fe atom forms three bonds with N atoms, while for the case of Cu 1 @C 2 N, the Cu atom prefers coordinating with two N atoms [48] (Figure S1, Supporting Information). These results are in line with previous theoretical findings.…”
Section: Geometries and Thermodynamic Stabilities Of The M 1 M 2 @C 2mentioning
confidence: 99%
See 3 more Smart Citations